Safety of Prescribing Statins in Childhood Dyslipidemia - Al-Alaili, Mohammed Khaled; Abdi, Abdikarim Mohamed; Basgut, Bilgen (Journal of Child Science, 2020)
Hyperlipidemia is on the rise in pediatrics, leading to early coronary artery disease complications. Familial hypercholesterolemia is an important risk factor, with the homozygous subtype being more dangerous, yet less prevalent than the heterozygous subtype. Statins are shown to be an effective treatment in this population. This systematic review will emphasize the safety of such drug class in pediatrics, while taking into consideration the latest cholesterol guideline. Cochrane Library, Clinicaltrials.gov, and PubMed were reviewed systematically in June 2019 and rechecked in November 2019 for the past 5 years with keywords like child, safety, hyperlipidemia, and statins, which resulted in nine randomized clinical trials. In short, statins are shown to be intermediately effective—median decrease of low-density lipoprotein cholesterol was 32% achieving the target of < 160 mg/dL in 67% of patients—in lowering lipid levels yet preventing early complications. They are also considered safely tolerated in most cases, even when taken for extended periods, but still not evidently permissible for children below 8 years old, which was the average age of all participants in the trials. Statins should not be given generally for pediatrics of less than 8 years old, in contrast to what was mentioned in the American Heart Association guideline (0–19 age range), since there is no evidence supporting their safety within this age group.
Keywords: statins; children; safety; familial hypercholesterolemia and hyperlipidemia